Financial Markets & Institutions, 13th Edition - Jeff Madura (Cengage Learning, 2020)
Develop a clear understanding of why financial markets exist, how financial institutions serve these markets, and what services those institutions offer with Madura's best-selling FINANCIAL MARKETS AND INSTITUTIONS, 13E. Packed with today's real examples and practical applications, this engaging edition clarifies the management, performance, and regulatory aspects of financial institutions. You explore the functions of the Federal Reserve System and its recent changes, major debt and equity security markets, and the derivative security markets. Expanded coverage now discusses stock valuation, market microstructure strategies, and liquidity in today's financial markets. In addition, new content explains popular sources of funding, such as crowdfunding. Real examples connect concepts to today's financial trends as online resources in MindTap digital learning solution highlight Excel Online, an integrated eBook, Aplia homework tools, and resources for strengthening your understanding.